(untitled) (Ozone Therapy Global Journal, 2022)
Fibrocartilaginous embolism myelopathy is a vascular disease that causes embolism of material from the nucleus pulposus originating in the intervertebral disc, resulting in interruption of the medullary blood supply with consequent ischemia. There is evidence that with a neurorehabilitation protocol, the patient has great improvements in the evolution of the clinical condition. The use of ozone, with its analgesic, anti-inflammatory and systemic properties, helps in the treatment, resulting in good prognosis with rapid improvement. In this work, a case report of a 10-year-old dog diagnosed with myelopathy due to fibrocartilaginous embolism will be addressed, where steroidal anti-inflammatory, antioxidant and neuroprotective medications were used, along with ozone sessions, with favourable evolution of symptoms